IMPLEMENTASION OF STEM-BASED EDUCATION FOR SUSTAINABLE DEVELOPMENT TO DEVELOP SUSTAINABLE AWARNESS IN ELEMENTARY SCHOOLS - Alvina Martha Sintiya; Luthfi Fakhru Ahsani, Eva (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Sustainability awareness is the expected outcome with the implementation of STEM-based ESD (Education for Sustainable Development) in the TOGA (Family Medicinal Plants) planting project. ESD is a role in education as a form of effort to achieve SDGs (Sustainable Development Goals). This study aims to describe the implementation of STEM-based ESD and to determine the sustainability awareness of grade 4 students of MI Sultan Fattah Jepara. This study is included in descriptive qualitative research. Where the type of research is field research. Data will be obtained through observation, questionnaires, and documentation. Data analysis to be carried out includes data reduction, data display and verification. The results of this study indicate that STEM-based ESD has been implemented by teachers in grade 4 students of MI Sultan Fattah Jepara with the TOGA planting project. The ESD indicator shows that sustainability and adaptation have a high value of 4, indicating that this indicator is successful in the TOGA project. Revitalization has a score of 2, indicating that students have difficulty reviving or repairing existing systems. Ecoliteracy with a score of 3, indicates an awareness of the importance of ecological understanding in the project. Students can develop sustainable awareness, as seen from the sustainable awareness indicators, namely behavioral awareness which has a score of 4.875, followed by the attitude awareness indicator with a score of 4.0625, and the emotional awareness indicator with a score of 2.0625.